A METHODOLOGY OF OPERATIVE DIAGNOSTICS OF THE RHYTHMIC WORK OF MINING ENTERPRISES ACCORDING TO THE DYNAMICS OF ELECTRICITY CONSUMPTION (INNOVATIVE ECONOMY, 2023)
Kochura D.V. A METHODOLOGY OF OPERATIVE DIAGNOSTICS OF THE RHYTHMIC WORK OF MINING ENTERPRISES ACCORDING TO THE DYNAMICS OF ELECTRICITY CONSUMPTIONPurpose. The aim of the article is the development of a methodology for separate operational diagnostics of the rhythmicity of the work of several quarries working as part of a mining and transport complex, which makes it possible to assess the contribution of each quarry to the formation of the production cost of a mining enterprise.Methodology of research. The research methodology includes the analysis of known methods and formulas for estimating the rhythmicity of a mining enterprise by the volume of products produced in a finite period of time, the transition in known formulas from the volume of products through the specific consumption of electricity to the consumption of electrical energy and electrical power per unit of time. The methods of spectral analysis, electrical engineering and energy management were used in the development of the method of assessing the rhythmicity of the mining and transport complex.Findings. The diagnosis of the rhythmicity of the work of each of the quarries operating in one mining and transport complex of the mining enterprise was carried out according to the dispersion of fluctuations of the electrical active power consumed by the crushing plant in the range of operating frequencies characteristic of each quarry. The dependence of the resonance frequencies of the spectral density of the fluctuations of the electrical power parameters of the crushing plant on the periods and volumes of ore supply from each pit of the mining enterprise was established. A methodology of separate operational assessment of the rhythmicity of the work of several quarries of a mining enterprise based on the dynamics of energy consumption of a crushing plant was developed, which allows to assess the rhythmicity of the work of each quarry and the mining and transport complex of the mining enterprise as a whole and to manage it.Originality. For the first time, the dependence of the resonance frequencies of the spectral density of fluctuations in the power consumption dynamics of the crushing plant on the periods of ore supply from each pit of the mining enterprise was established.Practical value. The developed methodology allows quickly to manage the logistics parameters of the supply of ore from the quarries of the mining enterprise, to increase the rhythm of production and to reduce the cost of production.Key words: rhythmicity of production, quarries, mining enterprises, cost of production, diagnostics.
Keywords: rhythmicity of production; quarries; mining enterprises; cost of production; diagnostics.